Application of Carbon Dots as Corrosion Inhibitor: A Systematic Literature Review - Muhamad Jalil Baari; Ravensky Yurianty Pratiwi (Universitas Gadjah Mada, 2022)
Corrosion is spontaneity and unavoidable reactions which cause degradation in the quality of the materials. Most industries have been harmed by the corrosion of manufacturing equipment. Several methods can be applied to control this problem. The use of corrosion inhibitors is an effective and practical way to decrease metal deterioration significantly. Many commercial inorganic and organic compounds are effective inhibitors, but most of them are not completely safe and relatively expensive. Carbon dots and their derivatives are potential compounds for resolving corrosion reactions on metal surfaces. Carbon dots can be synthesized from various natural sources to be more environmentally friendly. This systematic review aims to summarize the concept of corrosion, types of carbon dots-based corrosion inhibitor and their effectiveness on various metals, inhibition mechanism, surface analysis of the protected metals, kinetics, thermodynamics, and quantum computational chemistry studies. This review also presents the significance and the prospects of carbon dots-based corrosion inhibitors.